EXPECTANCY BELAJAR MAHASISWA PENDIDIKAN LUAR SEKOLAH FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Akmal Adi Putra; Jasfar Jas; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research was the curiosity of researchers that a student outside of school education the Faculty of Education University of Riau. Formulation of the problem how is the level of expectation of Student Learning School Education FKIP UR ?. The purpose of this study to know how high Expectancy Student Learning School Education the Faculty of Education University of Riau. This type of research is descriptive with quantitative approach. The respondents of this study amounted to 67 students and 20 people on a trial basis. Data collection instruments consisted of a questionnaire consisting of 52 items statement. The research instruments included therein research variables are Expectancy learn indicator consists of (1) The confidence; (2) Effectiveness of self; (3) Motivation; (4) Ability.Key words: Expectancy, Learning, students of school education.